TRACE ELEMENT GEOCHEMISTRY OF THE 1991 MT. PINATUBO SILICIC MELTS, PHILIPPINES: IMPLICATIONS FOR ORE-FORMING POTENTIAL OF ADAKITIC MAGMATISM - Borisova A.Yu.; Polvé M.; Freydier R.; Candaudap F.; Pichavant M.; Wiedenbeck M. (My University, 2006)
The dacite pumice erupted from Mt. Pinatubo on June 15, 1991 (whole-rock, rhyolitic groundmass glasses and homogenized melt inclusions) has been analyzed using inductively coupled plasma-mass spectrometry (ICP-MS), nanosecond and femtosecond laser ablation ICP-MS and secondary ion mass spectrometry (SIMS) to evaluate its ore-forming potential. Data suggest that adakite magmas are metal-rich and concentrate ore metals during magmatic differentiation. Sulfides segregate in limited amounts under the hydrous, oxidizing conditions typical of adakitic magmas resulting in incompatible behavior for Au (6-22 ppb), Cu (26-77 ppm), and Pb, Mo, As, and Sb in melts of dacitic to rhyolitic compositions. Metal transfer from this adakite magma to the coexisting aqueous phase was favored by the peraluminous composition of the rhyolitic melt and high aqueous chloride concentrations. Mass balance calculations suggest that the pre-eruptive aqueous phase could have extracted a minimum of 100 t Au and 5 × 105 t Cu from the Mt. Pinatubo magma. Our data suggest that intrusives having adakitic signatures are genetically associated with Au-Cu and Cu-Mo mineralization, auriferous porphyry copper deposits, and epithermal gold veins. High H2O, Cl, Sr/Y, Pb/Ce, Mo/Ce, As/Ce and Sb/Ce in Mt. Pinatubo melts reflect the contribution of deep fluids derived from subducted sediments and altered MORBs in the dacite genesis. The slab-derived fluids carrying mobile elements are likely responsible for the enrichment of adakite magmas in gold, associated metals and H2O, and may explain the exceptional ore-forming potential of adakite magmatism. © 2006.